Intraoperative End-Tidal Carbon Dioxide Concentrations: What Is the Target? - Megan Way; Gary E. Hill (Anesthesiology Research and Practice)
Recent publications suggest that target end-tidal carbon dioxide concentrations should be higher than values currently considered as acceptable. This paper presents evidence that end-tidal carbon dioxide values higher than concentrations that are currently targeted result in improved patient outcomes and are associated with a reduced incidence of postoperative complications.